Analisis Sentimen Kepuasan Pengguna My Jne App Menggunakan Metode Support Vector Machine (SVM) Dan NaÃ¯ve Bayes Classifier (NBC) - Aulawi, Hilmi; Kurniawati, Rina; Permana, Yogi (Institut Teknologi Garut, 2024)
The aim of this research is to find problems with PT's goods expedition services. The first Tiki Lintas Nugraha (JNE), as well as the solution to this problem, based on reviews on various social media about PT's performance and services. The first Nugraha Line Tiki (JNE). Sentiment analysis is the computational study of a person's opinions, behavior, and emotions toward highly debated events or issues in society. One of the highly debated issues in 2021 is the policy of the My JNE Application system and social media as customer service for shipping goods. Of the two classification methods, the one with the highest accuracy value was selected. In this research, the Naive Bayes Classifier method is used to determine class groups of text documents. This method shows a fairly high level of accuracy, with a value of 97.67%. Next, the most common problems found based on the appearance of negative words were analyzed using text association. There are four main topics of many problems. The Analytic Network Process (ANP) process is used in the next stage to determine the solution priority from the output of the first stage to determine the solution priority level. Solutions that can be applied to My JNE system policy problems and social media customer service related to freight forwarding services include system improvement strategies and application maintenance that many complain about. Strategy to improve the skills of couriers and employees, strategy to improve employee and courier performance, strategy to strengthen the lost package policy by replacing lost items with the same amount, and strategy to provide punishment to couriers and employees if they make a mistake.